(untitled) (Kronika Bydgoska, 2020)
Lieutenant Colonel Jan Nepomucen Sławiński rendered great service to Bydgoszcz and its region, but he is almost unknown in the city on the Brda River. Brief biographical information on Sławiński can be found in only a few reports, primarily for the needs of dictionaries. He is vividly remembered as a hero of the Wielkopolska Uprising 1918-1919, distinguished by his field actions and work as a staff member on the Noteć River front. Just before the outbreak of World War II, he served as commander of Bydgoszcz, which tasks included maintaining peace and order in the city in case of war. Even before the beginning of warfare, he handed over the command of the city to Maj. Wojciech Albrycht, becoming the commander of the 82nd Guard Battalion, with which he traveled the entire combat trail of the September 1939 Campaign until the formation was defeated by the Wehrmacht in the Sochaczew area. He was an exemplary Polish citizen throughout his life - a patriot and officer of the Polish Army, who became a hero fighting for the independence of the Homeland, decorated for his dedication with the Silver Cross of Virtuti Militari. His parents instilled a sense of patriotism and love of the Homeland in him, which was later reinforced during his youth activities in Tomasz Zan’s Society and scouting. It was layer strengthened and turned into military skills during his service in the Imperial Army during World War I, which were very useful in 1919-1920 and 1939.